The Impact of Utilizing Digital Mapping Technology in Optimizing Urban Waste Transportation for the Environmental Quality Index - Ayuningsih, Ekatri; Yamaputra Anagata, Riko (Badan Perencanaan Pembangunan Kota Malang, 2024)
This study explores the use of digital mapping technology to optimize waste transportation routes in Malang City, Indonesia. By utilizing GIS (Geographic Information System) applications, this study aims to improve operational efficiency and reduce waste transportation costs. Through field observation and statistical analysis methods, it was found that this technology can reduce travel distance by up to 15% and travel time by up to 25%. These results show significant potential in reducing operational costs and carbon emissions, as well as supporting environmental sustainability goals. However, challenges such as workforce resistance to new technologies and limited costs and data access still need to be addressed through training and supportive policies. This study provides important implications for waste managers and local governments to design more efficient and environmentally friendly waste management strategies, and encourage wider adoption of digital technologies. These findings offer evidence-based recommendations for policy makers to improve the quality of urban waste management through technological innovation.